CRITICAL ANALYSIS OF ISLAMIC POPULISM: Insights from Indonesian Perspectives (State Islamic University (UIN) of Sunan Ampel Surabaya, 2024)
This study aims to provide an alternative insight into understanding Islamic populism. Previously, there has been a long debate about how to frame Islamic populism in Indonesia. The first approach tends to believe that Islamic populism is a product of economic inequality, while the second approach underlies the increasing use of religious identity to mobilize people. Considering both sides, this paper used critical review analysis to find out the gap amidst the existing literature. The result shows that, Islamic populism within the Indonesian context seems to be an emotional movement among especially urban Muslim middle class in that attempts to bring religion into line with dogmatic political preferences. They frustrated with existing Islamic political parties which they considered abandoning true Islamic agenda such as implementation of Islamic law and Islamic leadership so that they resorted to populism. This attitude has grown up recently, especially to 212 movement, “Aksi Bela Ulama” and “Aksi Bela Islam” to keep Islam as the majority.